2020
DOI: 10.1186/s12879-020-05336-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic utilization in hospitalized children under 2 years of age with influenza or respiratory syncytial virus infection – a comparative, retrospective analysis

Abstract: Background Infections due to Respiratory Syncytial Virus (RSV) and Influenza virus (FLU) are leading causes of hospitalization in young children. Yet, there is little data on factors associated with antibiotic use in these patients. Methods We conducted a retrospective, single-center study of all patients below 2 years of age hospitalized between 2014 and 2018. We compared children with RSV infection to children with FLU infection analyzing clinical characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…Our study found that, with the exception of the 37–60 months old age group, the proportion of length of hospital stay≥7 days in the other age groups was greater than 62.0%. However, Papan et al 18 found that the average hospital stay was about 5 days in a study of hospitalized children under 2 years of age with RSV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that, with the exception of the 37–60 months old age group, the proportion of length of hospital stay≥7 days in the other age groups was greater than 62.0%. However, Papan et al 18 found that the average hospital stay was about 5 days in a study of hospitalized children under 2 years of age with RSV infections.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the complexity of a diagnosis leads to potentially disregarded CoNS infections, consequently leading to undertreatment (i.e., delayed or withheld antibiotics) in some cases and thereby contributing to morbidity and mortality [ 45 ]. On the other hand, antibiotic overtreatment is associated with the development of antimicrobial resistance, severe adverse events, and higher costs, mainly due to the need for in-patient therapy [ 46 ]. Ultimately, an unnecessarily prolonged hospitalization does not only cause a loss in quality-adjusted life-years, but hospital bed occupancy exposes another factor of this complexity, which becomes particularly immanent during times of hospital capacity shortage, especially during pandemics, such as COVID-19 [ 47 ].…”
Section: The Diagnostic Complexities—how To Distinguish Between Infection and Contaminationmentioning
confidence: 99%
“…10,11 Similar patterns were identified in previous observational studies examining antibiotic misuse for patients with viral respiratory infections. 22,26 Interestingly, we identified that female sex is an influential predictor for unnecessary antibiotic treatment. Higher rates of antibiotic overprescription were previously reported for adult women, even when correcting for prevalence of conditions necessitating antibiotic therapy (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…These numbers are in the range of estimates observed in other studies, although between-study variability is high. 9, [19][20][21][22][23][24][25] Using a multivariate logistic model, we found predictors that explain some of the physicians' decision making process leading to administration of unnecessary antibiotic therapy. Drawing of blood, urine or CSF cultures had substantial associations with unnecessary antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation